A fishy gut feeling – current knowledge on gut microbiota in teleosts - Tolas, Ingvill; Zhou, Zhigang; Zhang, Zhen; Teame, Tsegay; Olsen, Rolf Erik; Ringø, Einar; Rønnestad, Ivar (Frontiers in Marine Science, 2025)
The importance of the gastrointestinal microbiota (GM) in health and disease is widely recognized. Although less is known in fish than in mammals, advances in molecular techniques, such as 16S rRNA sequencing, have facilitated characterization of fish GM, comprising resident autochthonous and transient allochthonous bacteria. The microbial diversity and composition are strongly influenced by diet. High-protein diets, including alternative ingredients like plant and insect proteins, modify GM, impacting beneficial bacteria e.g. Cetobacterium. Lipids affect microbial metabolism and short-chain fatty acid (SCFA) production, while excessive carbohydrates can disrupt GM balance, causing enteritis. Dietary additives, including probiotics, prebiotics, and antibiotics, effectively modulate GM. Probiotics enhance immunity and growth, prebiotics support beneficial bacteria, and antibiotics, though effective against pathogens, disrupt microbial diversity and may promote antibiotic resistance. Environmental factors, such as temperature, salinity, and pollution, significantly influence GM. Elevated temperatures and salinity shifts alter microbial composition, and pollutants introduce toxins that compromise intestinal function and microbial diversity. Stress and pathogen infections further destabilize GM, often favoring pathogenic bacteria. GM communicates with the host via metabolites such as SCFAs, bile acids, and neurotransmitters, regulating appetite, energy metabolism, immunity, and neural functions. Additionally, GM influences the immune system by interacting with epithelial cells and stimulating immune responses. Despite recent advances, further research is needed to elucidate species-specific mechanisms underlying GM-host interactions, the ecological implications of GM diversity, and its applications in aquaculture to optimize fish health and performance.